Capacity of two cell lines for the production of cloned embryos by nuclear somatic c ell transfer - Cortez, Jenin (2017)
This study demonstrates the use of nuclear somatic cell transfer to produce the first cloned cattle in Peru. Skin fibroblasts and cumulus cells from adult donors were obtained for use as carioplasts; likewise, oocytes obtained from ovaries in the slaughterhouse were matured in vitro for 24 h. The mature oocytes were incubated 2 h in demecolcin (2.5 μg/ml) to promote cone formation with the metaphase plate and to guide manual enucleation. The zona pellucida in pronase (2 mg/ml) was removed for 3 min. The enucleation was manual with a microblade dividing the ova into two halves, where the nucleus-lacking halves were fused by the «sandwich» method (cytoplast–fibroblast– cytoplast). The reconstructed structures were chemically activated by incubation for 5 min in 7% absolute ethanol, followed by 5 h of cytochalacin B (5 μg/ml) and cycloheximide (10 μg/ml). The structures were cultured for 7 d until the blastocyst incubation/hatching phase. Seven blastocysts were transferred to six synchronized recipient cows seven days after ovulation. The permanence of four and three embryonic vesicles was achieved until days 28 and 60, respectively. Two calves were born from embryos reconstructed with skin cells and cumulus cells. By the genotype analysis using 15 markers (SSR) for cattle, it was confirmed that cloned calves were derived from donor cell lines.